More Yield is Better - Less Nitrate is Better (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article describes the impact of nitrogen fertilizers on the environment, especially on human health. Excessive use of fertilizers is highlighted on the basis of data obtained when the permissible concentration of nitrates in the product is exceeded. The increase in nitrates in the composition of the product depends on the type of nitrogen fertilizers, as well as their use during the growing season, as well as external and internal factors that affect the accumulation and decrease of nitrates in the plant body. For example, it has been found that the amount of nitrate nitrogen in root crops depends on the number of their stems and the size and size of root crops. The influence of tillage on the content of nitrates in vegetable crops was also revealed.